Childhood caries as influenced by maternal and child characteristics in pre-school children of Kerala-an epidemiological study - N Retnakumari; Gibi Cyriac (Wolters Kluwer Medknow Publications, 2012)
Purpose: The most common chronic disease of childhood is early childhood caries which is five times more prevalent than asthma and seven times higher than that of allergic rhinitis. Most children do not receive dental care until they are three years old, yet by the time more than thirty percent of children from lower socioeconomic groups already have caries. To determine the prevalence and severity of early childhood caries among pre-school children, to describe the child characteristics associated with the development of early childhood caries and to find the association of early childhood caries and maternal risk factors. Materials and Methods: This descriptive study was carried out among children attending the immunization clinic of Sree Avittam Thirunal Hospital, Medical College, Trivandrum and children attending the randomly selected Anganwadies and Day care centres in Trivandrum, the capital of Kerala, wherein there are migrants from all over the State. A total of 350 children aged 12-36 months and their mothers were studied. The mother was first interviewed by a structured questionnaire; then the child's and mothers clinical examination was carried out covering caries experience and oral hygiene status. Results: Among 350 children studied the prevalence of dental caries in this study population was found to be 50.6 %( 177). Statistically significant associations were found between the severity of decay and the child's age(P<0.001), female gender(P<0.05),low socioeconomic status (P<0.05), feeding frequency (P<0.05), type of feeding(P<0.01), fell asleep with nipple in mouth (P<0.05), duration of breast feeding(P<0.001), consumption of cariogenic type of snacks(P<0.01), age of commencement of tooth brushing(P<0.05), brushing frequency(P<0.05), oral hygiene status of child(P<0.001), DMFS scores of mothers (P<0.001), and oral hygiene status of mother (P<0.001).